The Interplay of Leadership Style, Competence, and Work Stress in Shaping Employee Performance: The Mediating Role of Job Satisfaction - Anggraini, Lenny; Yuli Budiati; Hardani (Journal of Educational Management Research, 2025)
The research conducted has the aim of examining the influence of Leadership Style, Competence, and Job Stress on Employee Performance and using job satisfaction as an intervening variable. This research includes the type of explanatory research, by distributing questionnaires in the form of open and closed questions to employees of Bank Muamalat Semarang as many as 60 people. And included in quantitative research.  The analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS approach. The sampling method uses the census method. The results of this study indicate that job satisfaction can mediate the relationship between leadership and employee performance with a P-value of 0.004 < 0.10. In addition, job satisfaction also significantly mediates the relationship between job stress and employee performance with a P-value of 0.001 < 0.10. Meanwhile, the competency variable cannot be mediated by job satisfaction, due to the lack of a direct influence between the competency variable and job satisfaction with a P-value of 0.584 > 0.10.